Trends of atherosclerosis-related mortality in adults with diabetes: A cross-sectional analysis of U.S. national data - Yusuf Hasan Ali; Fakhar Latif; Fatimah Hoda; Azeem Hassan; Huda Ahmed; Raheel Ahmed; Vikash Jaiswal (Atherosclerosis Plus)
Background: Diabetes mellitus is a rapidly growing global health issue, projected to affect 643 million adults by 2030. Atherosclerosis, a prevalent complication of diabetes, significantly contributes to morbidity and mortality among affected individuals. This study aimed to analyze mortality trends associated with atherosclerosis in diabetic patients aged ≥45 years, with particular focus on variations by sex, race, urban-rural classification, and geographical regions in the US from 1999 to 2020. Methods: We conducted a study using data from the CDC WONDER database, identifying atherosclerosis-related deaths in diabetic patients. We calculated age-adjusted mortality rates (AAMRs) per 100,000 population and analyzed trends over time using Joinpoint regression to assess annual percentage changes (APC) and average annual percentage changes (AAPC). Results: A total of 674,582 atherosclerosis-related deaths were recorded in diabetic patients from 1999 to 2020, with a higher prevalence in men (57.40 %). The majority of deaths occurred in NH White individuals (81.70 %). Overall, AAMRs declined from 32.8 in 1999 to 25.8 in 2020. A significant decrease was observed from 1999 to 2014 (APC: −2.61, p < 0.05), followed by stability (2014–2018) and a subsequent rise (APC: 6.97, p < 0.05) till 2020. Sex-stratified analysis indicated persistently higher AAMRs in men, with a significant increase from 2018 to 2020 (APC: 7.33, p < 0.05). Racial disparities were evident, with NH Black individuals demonstrating the highest AAMRs. Geographic analysis revealed higher AAMRs in nonmetropolitan areas, with notable state-level variations. All census regions exhibited an initial decline, followed by a significant rise in AAMRs post-2018 (p < 0.05). Conclusion: Despite initial declines, recent trends indicate a resurgence in atherosclerosis-related mortality among diabetic patients, particularly in specific racial groups, rural areas, and certain regions. These findings underscore the need for targeted interventions to address disparities and improve cardiovascular outcomes in diabetic populations.